A biological approach to crown fracture: Fracture reattachment - A report of two cases - K Vijayaprabha; Nikhil Marwah; Samir Dutta (Wolters Kluwer Medknow Publications, 2012)
The development of adhesive dentistry has allowed dentists to use the patient's own fragment to restore the fractured tooth, which is considered to be the most conservative method of treatment of crown fracture allowing restoration of original dental anatomy, thus rehabilitating function and esthetics in a short time by preserving dental tissues. The tooth fragment reattachment is preferred over full coverage crowns or composite resin restoration because it conserves sound tooth structure, and is more esthetic, maintaining the original anatomy and translucency, and the rate of incisal wear also matches that of original tooth structure. Presented here is a report of two cases of crown fracture managed by reattachment procedures.